2021
DOI: 10.3390/ma14216666
|View full text |Cite
|
Sign up to set email alerts
|

Improved Non-Piezoelectric Electric Properties Based on La Modulated Ferroelectric-Ergodic Relaxor Transition in (Bi0.5Na0.5)TiO3-Ba(Ti, Zr)O3 Ceramics

Abstract: The characteristic transition from ferroelectric (FE) to ergodic relaxor (ER) state in (Bi0.5Na0.5)TiO3 (BNT) based lead-free ceramics provides an efficient approach to bring a highly ordered phase back to a disordered one. It would be rational to utilize this transition to improve relevant non-piezoelectric properties based on domain decomposition. In this work, different La contents were introduced to 0.93(Bi0.5Na0.5)TiO3-0.07Ba(Ti0.945Zr0.055)O3 ceramics (BNT-BZT-xLa) to induce evolution of ergodic degree. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…In addition, the samples exhibit an ultra-short t 0.9 (corresponding to a discharge time of 90% of the saturated W d value), which is 89 ns for the CS-sintered sample and 75 ns for the TSS-sintered sample. Both values are significantly lower than those in many other energy storage materials. ,,, The fast discharge rate of the 0.12La sample indicates that the material can release stored energy in a very short time, demonstrating its good application value. In addition, when comparing the charging and discharging performance between the CS- and TSS-sintered samples, the TSS-sintered sample exhibits a higher discharge rate, which can be related to its high energy storage efficiency.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, the samples exhibit an ultra-short t 0.9 (corresponding to a discharge time of 90% of the saturated W d value), which is 89 ns for the CS-sintered sample and 75 ns for the TSS-sintered sample. Both values are significantly lower than those in many other energy storage materials. ,,, The fast discharge rate of the 0.12La sample indicates that the material can release stored energy in a very short time, demonstrating its good application value. In addition, when comparing the charging and discharging performance between the CS- and TSS-sintered samples, the TSS-sintered sample exhibits a higher discharge rate, which can be related to its high energy storage efficiency.…”
Section: Resultsmentioning
confidence: 82%
“…Unlike linear and ferroelectric ceramics, relaxor ferroelectric ceramics generally have high P max , low P r , and moderate BDS, the characteristics that more likely provide high energy storage density. , Considering that the vast majority of traditional relaxor ferroelectric ceramics are lead-based materials detrimental to humans and the environment, research and development of lead-free energy storage materials have intensified in recent years. ,, Lead-free (Bi 0.5 Na 0.5 )­TiO 3 (BNT) ceramic is an important kind of relaxor ferroelectric ceramics, exhibiting a high dielectric constant and strong ferroelectricity. However, low BDS and large hysteresis with high P r hinder their energy storage applications. Common approaches for improving the energy storage performance of BNT-based materials are phase adjustment along with domain engineering and grain size control via doping or employing different processing methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In addition, the long-range ferroelectric order can be severely disrupted through La doping, which will contribute to the promotion of ergodicity degree and energy storage performance. [28][29][30][31] Zhang et al reported that the ergodic degree deepened with La content in a La-doped 0.93(Na 0.5 Bi 0.5 )TiO 3 -0.07Ba(Zr 0.055 Ti 0.945 )O 3 system, which resulted in "slimmer" P-E loops and enhanced η and W rec . 29 Yu et al added La to 0.78Na 0.5 Bi 0.5 TiO 3 -0.22K 0.5 Bi 0.5 TiO 3 ceramics and discovered that the ferroelectric order was largely disrupted by La doping and converted to an ergodic relaxation state.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] Zhang et al reported that the ergodic degree deepened with La content in a La-doped 0.93(Na 0.5 Bi 0.5 )TiO 3 -0.07Ba(Zr 0.055 Ti 0.945 )O 3 system, which resulted in "slimmer" P-E loops and enhanced η and W rec . 29 Yu et al added La to 0.78Na 0.5 Bi 0.5 TiO 3 -0.22K 0.5 Bi 0.5 TiO 3 ceramics and discovered that the ferroelectric order was largely disrupted by La doping and converted to an ergodic relaxation state. 30 In summary, the energy storage properties of lead-free ferroelectrics can be optimized by La doping.…”
Section: Introductionmentioning
confidence: 99%